Ecotourism Management and Economic Valuation of the Bahowo Mangrove Area: A Strategy for Revitalization into a Sustainable Tourism Destination - Oktavianus Lintong; Jeanlly A. Solang; Meiske M. Sangian; Easter Ch. M. Tulung (JURNAL ECONOMINA, 2026)
The Bahowo mangrove ecotourism area in Manado City has declined in economic and ecological value after its functional shift to a transit dock. This condition contradicts the principles of a sustainable tourism destination, which demands a balance among ecological, economic, and socio-institutional aspects. This study intends to evaluate existing conditions and formulate an ecotourism management strategy, grounded in economic valuation, integrity tourism, and the heptahelix model, to revitalize Bahowo as a sustainable tourism destination. The research approach combines physical carrying capacity analysis with the Contingent Valuation Method (CVM) to measure visitors' Willingness to Pay (WTP). The results show that the resource suitability level is classified as "unsuitable," with an index of 1.84, due to the complete destruction of tourist trail infrastructure (0%) and stagnation in institutional governance. However, the economic valuation analysis discloses a high potential for latent demand; the average visitor's willingness to pay for ecotourism packages is USD 4.75 per person. This financial finding delivers an economically rational justification for capital investment in infrastructure recovery, demonstrating viability and supporting the economic pillar of sustainability. The recommended revitalization strategy focuses on capitalizing on the WTP value through Integrity Tourism principles, implemented through the interaction of the Heptahelix Collaboration Model, which serves as the primary prerequisite for realizing a sustainable tourism destination.